PERILAKU MEROKOK PADA PASIEN HIPERTENSI DI RUMAH SAKIT UMUM DAERAH PALEMBANG BARI - Wahyudi, Joko Tri (IKesT Muhammadiyah Palembang, 2020)
Background of the research: Hypertension is the beginning of the catastrophic diseases. Hypertension kills almost 8 billions people each year in the world and almost 1,5 billions people each year in South-East Asia region. About a third of adult males in South-East Asia Region are having hypertension. One of risk factors that trigger hypertension is smoking. Smoking can cause Hypertension due to nicotine can stimulates the release of catecholamine which causes irritability, myocardial, the increase of heart beat and also causes vasoconstriction that lead to the increase of blood pressure. The purpose of this study is to identify the description of Smoking Behavior of Hypertentive Patients at Rumah Sakit Umum Daerah Palembang BARI. Methods of the research: Research design for this study was a quantitative research using descriptive analysis which aimed to describe the study object through data and the collected samples were 45 respondents. Results of the research: From the results of the study showed that from 45 respondents there were (13,1%) with Less Knowledge, (37,8%) with Adequate Knowledge, and (48,9%) with Good Knowledge. There were (8,9%) with Negative Behavior, and (9,1%) with Positive Attitude. Then (31,1%) with Less Good Behavior, (60,0%) with Adequate Action, and (8,9%) with Good Action. Discussion: Knowledge of hypertentive patients about smoking is categorized into good, patient’s behavior about hypertension is categorized into positive and smoking action of hypertension patients is categorized into adequately good.